Cultivating outdoor classrooms : designing and implementing child-centered learning environments - Nelson, Eric M. (St. Paul, MN : Redleaf Press, 2012)
"There are many ways outdoor spaces can be transformed into fully functioning classrooms where children explore, experiment, and spend quality time in nature. Filled with both simple and large-scale ideas, Cultivating Outdoor Classrooms provides support as you design and implement outdoor learning environments"--
Includes bibliographical references.
Keywords: Outdoor education; Outdoor education -- Study and teaching; Experiential learning; EDUCATION / Preschool & Kindergarten; NATURE / Ecosystems & Habitats / General